2017
DOI: 10.1111/eea.12571
|View full text |Cite
|
Sign up to set email alerts
|

Measuring host plant selection and retention of Halyomorpha halys by a trap crop

Abstract: Trap cropping may exploit a pest's dispersal and host selection behavior in order to protect a desired crop. Here, we used a combination of visual sampling, immunomarking, and harmonic radar to assess host plant selection and retention time of the highly mobile and invasive Halyomorpha halys (Stål) (Hemiptera: Pentatomidae), as it moves within and between a polyculture trap crop of sorghum and sunflower, and a bell pepper cash crop. Visual sampling demonstrated no significant differences in H. halys densities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…The pattern of food volatiles synergizing attraction to a pheromone has also been more broadly demonstrated as well; for example, with the boll weevil Anthonomus grandis (Dickens, ). Taken together with prior data (Acebes‐Doria et al ., ; Morrison et al ., 2016; Blaauw et al ., ), the present study strongly indicates that host stimuli (construed broadly as the visual, auditory, gustatory, thermal and volatile stimuli) are important for the foraging of H. halys .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The pattern of food volatiles synergizing attraction to a pheromone has also been more broadly demonstrated as well; for example, with the boll weevil Anthonomus grandis (Dickens, ). Taken together with prior data (Acebes‐Doria et al ., ; Morrison et al ., 2016; Blaauw et al ., ), the present study strongly indicates that host stimuli (construed broadly as the visual, auditory, gustatory, thermal and volatile stimuli) are important for the foraging of H. halys .…”
Section: Discussionsupporting
confidence: 63%
“…However, even for such a generalist, previous work has demonstrated that certain crop species, such as sorghum and sunflower, are more attractive than other crops to H. halys (Nielsen et al ., ). Specifically, a trap crop of sunflower and sorghum has been shown to be promising in attracting and retaining H. halys adults compared with a cash crop of bell pepper (Soergel et al ., ; Blaauw et al ., ). Acebes‐Doria et al .…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, applying an attraction index allowed correction of unidirectional movement toward the same host plant as released from, accounting for natural dispersal behaviors. Adult stink bugs readily move between host plants (Jones and Sullivan, 1982;Tillman et al, 2009;Aigner et al, 2017;Blaauw et al, 2017), and the results from this work demonstrate that H. halys nymphs can also move amongst host plants. While nymphs are generally the more vulnerable stage of pentatomids, finding an adequate food resource may outweigh the risk of dispersing from their oviposited location.…”
Section: Discussionmentioning
confidence: 57%
“…Host attractiveness changes depending on host species and plant phenology, which is likely influenced by visual and olfactory cues. Thus, crop layout and trap crop utilization (Blaauw et al, 2017), in addition to chemical attractants (Weber et al, 2017;Morrison et al, 2018b), may also be used in pest management strategies for H. halys. Furthermore, four VOCs were identified here that were associated with highly attractive host plants, which is encouraging for the future understanding of dispersal cues and attractants.…”
Section: Discussionmentioning
confidence: 99%
“…Sunflower alone used as a trap crop for peppers did not reduce injury (132); the use of sorghum plus sunflower as trap crop species attracted BMSB, although injury to organic peppers was only minimally reduced (92). The use of harmonic radar and protein markers to quantify retention within the sunflower and sorghum trap crop showed that the trap crop itself was more attractive than the pepper cash crop but did not act as a population sink (22).…”
Section: Exploiting Behavioral Ecology Several Studies Have Measuredmentioning
confidence: 96%